An introduction to Yōkai culture - Kazuhiko, Komatsu (Japan Publishing Industry Foundation for Culture, 2017)
Since ancient times, the Japanese have lived with superstitions of strange presences and phenomena known as "yokai," creating a culture by turns infused with unease, fear, and divinity. Tsukimono spirit possessions. Fearsome kappa, oni, and tengu. Yamauba crones. Ghostly yurei. Otherworldy ijin...Where did they come from? Why do they remain so popular? Written by Japan's premier scholar of yokai and strange tales, this book is both an introduction to the rich imagination and spirituality of Japan's yokai culture and a history of the authors and writings that have shaped yokai studies as a field.